Implementation of Lean Manufacturing Tools for Material Management in a Warehouse - Realyvásquez Vargas, Arturo (2025)
This article presents a case of a company dedicated to the sale, installation, and service of air conditioning and heating. The company has no internal inventory control in its warehouses. In the period 2022-2023, a total of 3 043 problems related to warehouse management were recorded, with an average of 84,53 problems/month. These deficiencies have led to economic setbacks, project delays, inadequate delivery times and the impossibility of guaranteeing their quality certification objectives in the short term. The objective of this study is to reduce these problems. As a methodology, lean manufacturing tools such as 5S, kaizen and kanban are implemented. After the implementation of the improvement, the problems in the warehouses were reduced to 79, with an average of 26,3 problems/month by the end of June and beginning of November 2023. It is concluded that the application of lean manufacturing tools improves efficiency rates in warehouse management.